Isolation and Characterization of Six AP2/ERF Transcription Factor Genes in Chrysanthemum nankingense - Gao, Chunyan (Int J Mol Sci, 2015)
The AP2/ERF family of plant transcription factors (TFs) regulate a variety of developmental and physiological processes. Here, we report the isolation of six AP2/ERF TF family genes from Chrysanthemum nankingense. On the basis of sequence similarity, one of these belonged to the Ethylene Responsive Factor (ERF) subfamily and the other five to the Dehydration Responsive Element Binding protein (DREB) subfamily. A transient expression experiment showed that all six AP2/ERF proteins localized to the nucleus. A yeast-one hybrid assay demonstrated that CnDREB1-1, 1-2 and 1-3 all function as transactivators, while CnERF1, CnDREB3-1 and 3-2 have no transcriptional activation ability. The transcription response of the six TFs in response to wounding, salinity and low temperature stress and treatment with abscisic acid (ABA), salicylic acid (SA) and jasmonic acid (JA) showed that CnERF1 was up-regulated by wounding and low temperature stress but suppressed by salinity stress. The transcription of CnDREB1-1, 1-2 and 1-3 was down-regulated by ABA and JA to varying degrees. CnDREB3-1 and 3-2 was moderately increased or decreased by wounding and SA treatment, suppressed by salinity stress and JA treatment, and enhanced by low temperature stress and ABA treatment.